1999
DOI: 10.1007/s004360050517
|View full text |Cite
|
Sign up to set email alerts
|

Development of Blastocystis hominis cysts into vacuolar forms in vitro

Abstract: The development of cysts of Blastocystis hominis isolated from human feces by the Ficoll-Paque concentration method and cultured in Jones' medium containing 10% horse serum is described. The morphological changes were studied by light and transmission electron microscopy at different intervals for up to 48 h. The cysts developed into a large number of vacuolar forms within 24 h, and binary fission was the only mode of reproduction observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
0
26
1
3
Order By: Relevance
“…TEM studies of the development of cysts to vacuolar forms were elegantly demonstrated with a human isolate and a rat isolate (46,153). In those reports, fecal cysts from both humans and rat develop similarly and dramatically into vacuolar forms within 24 h of inoculation into growth medium.…”
Section: Life Cyclementioning
confidence: 96%
See 4 more Smart Citations
“…TEM studies of the development of cysts to vacuolar forms were elegantly demonstrated with a human isolate and a rat isolate (46,153). In those reports, fecal cysts from both humans and rat develop similarly and dramatically into vacuolar forms within 24 h of inoculation into growth medium.…”
Section: Life Cyclementioning
confidence: 96%
“…21,2008 CLINICAL ASPECTS OF BLASTOCYSTIS SPP. 645 strain variations, or they are possibly cells in various stages of encystation or excystation, as similar morphologies were described in TEM studies of cells undergoing excystation (46,153).…”
Section: Morphological Formsmentioning
confidence: 99%
See 3 more Smart Citations